Impacto del turismo en el catastro de los establecimientos turísticos del cantón Quevedo, año 2021 - Mesias Sanchez, Emily Valeria (2021)
Tourism is an activity that involves the direct participation of the human being, since different activities are developed that derive from it. This implies that the human being must relate with nature, coexistence with other cultures and traditions, way of life of other people, among other manifestations that directly attract tourists. In the Province of Los Rios is located the Canton Quevedo, a sector that has the necessary characteristics for the development of a tourist guide that influences the tourist development of the cantonal capital. In the development of this research work we propose to analyze the impact of tourism in the cadastre of tourist establishments located in the Canton of Quevedo, since this is a very relevant factor when implementing an establishment in any part of the country. It is for this reason that an analysis of the cadastre is proposed since it should not directly affect tourism and the establishments that are already implemented in the canton and those that are coming in the future.